PENGARUH PENERAPAN ANGARAN BERBASIS KINERJA DAN PENGENDALIAN INTERN TERHADAP KINERJA KEUANGAN PEMERINTAH DAERAH KOTA PEKANBARU - Sahri, Hasri Raka; Agusti, Restu; A, Alazhar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
This study aimed to examine the effect of the application of Performance-Based Budgeting and Financial Performance Against Internal Control in the regional work units in the city of Pekanbaru. Research carried out on 32 working units in the city of Pekanbaru in 2015. The samples were used as respondents are taken using the method of sampling proposive. Each population represented by three respondents, namely the head SKPD, head of sub-department of finance and Head of Program. Questionnaires were distributed to 96 respondents, and successfully recovered the complete answer is obtained from 75 respondents. Data were collected from 75 respondents further data were analyzed with SPSS version 17.0 using descriptive statistical analysis and multiple linear regression analysis to produce the classic assumption test, model of data analysis, coefficient of determination and prove the hypothesis. Partial results of the study found that the variable performance-based budget and the Internal Control effect on financial performance.Keywords: budgeting, control, and financial performance.